Efficacy and safety of interferon alfa-2b in the complex therapy of patients with chronic bacterial prostatitis: a multicenter randomized clinical trial - Kh. S. Ibishev; M. I. Kogan; V. V. Dubensky; Vl. V. Dubensky; I. S. Shormanov; A. S. Soloviev; I. V. Bazhenov; D. V. Romanenko; E. N. Vyzhlova (Лечащий Врач)
Chronic bacterial prostatitis reduces the reproductive function of men and worsens the quality of life. Impairment of the immune system in chronic bacterial prostatitis requires immunocorrection and use of additional immunomodulatory therapy. The objective of this multicenter, double-blind, randomized, placebo-controlled clinical trial was to prove the efficacy and safety of the recombinant interferon alpha-2b preparation and highly active antioxidants (vitamins E and C) in complex therapy in patients with chronic bacterial prostatitis. Men aged 18 to 50 years with a diagnosis of chronic bacterial prostatitis of category II or IIIA (N = 140) were randomized into two groups. Patients in the main group (N = 70) received interferon alpha-2b, rectal suppositories 1,000,000 IU (20 days bid), and patients in the comparison group (N = 70) received placebo as described above. All patients received levofloxacin (500 mg/day, 28 days) as antibiotic therapy. The efficacy of treatment was assessed by clinical questionnaires, bacteriological and microscopic analyses, frequency of chronic bacterial prostatitis relapses within 6 months from the start of treatment, and by ultrasound and urodynamic testing. The efficacy was evaluated at the end of additional therapy, at the end of antibiotic therapy and six months after the start of treatment. Clinical symptoms of chronic bacterial prostatitis decreased in both groups within 20 days after the start of treatment. However, interferon alpha-2b therapy reduced the average number of leukocytes in the prostate secretion/third urine specimen by 2.6 (95% CI: 1.6-4.4) times by the end of interferon therapy, by 4.2 (95% CI: 2.4-7.2) times by the end of antibiotic therapy and by 5.4 (95% CI: 3.4-8.3) times by the end of follow-up period compared to placebo (p < 0.001). The proportion of patients with prostate secretion microbiota was 20% lower in interferon alpha-2b compared to Placebo group (p = 0.013). Thus, complex interferon alpha-2b therapy improved chronic bacterial prostatitis resolution by accelerating the elimination of bacteria and reducing inflammatory and proliferative processes in the prostate. Interferon alpha-2b had no safety concerns and was well tolerated by patients.